Spray-air contact in tall and short-type spray dryers affects important physicochemical properties of microencapsulated chia seed oil - Bordón, María Gabriela (2020)
The aim of this work was to determine the influence of the spray dryer`s aspect ratio (height/diameter) on the physico-chemical properties of microencapsulated chia oil (CSO). Two different dryers were analyzed: a tall-type dryer [H/D = 5/1], and a short-type dryer [H/D = 1.65/1]. The former corresponded to a co-current flow, while the latter had a central air disperser in the chamber, and a rotary air flow. Emulsions were prepared by homogenization of CSO, and a mixture of soy protein isolate (SPI) and gum arabic (GA). The co-current contact in the tall-type dryer yielded greater oxidative stability indexes (OSI) (three times higher than CSO), which was possibly associated the reduced thermal degradation. It can be concluded that a co-current contact constitutes a better alternative for the protection of CSO.